Leveraging TikTok virtual gifts for rural infrastructure funding: A case study from Sampang Village, East Java, Indonesia - Koswara, Asep (Social Sciences Insights Journal, 2025)
This study explores the use of TikTok virtual gifts as a novel approach to funding rural infrastructure projects in East Java, Indonesia, focusing on the village of Sampang. The initiative, driven by local residents, utilized funds gathered from viral TikTok donations to repair damaged roads in the region. Through qualitative observation and thematic analysis of secondary data from news sources like Detik.com, this research examines the dynamics of community-led funding, social media influence, and the limitations of traditional government support. The findings highlight the significant role of digital platforms in empowering rural communities, overcoming bureaucratic delays, and fostering collective action. Despite the success of this initiative, questions remain regarding sustainability, transparency, and the future role of digital fundraising in rural development. This paper contributes to the understanding of how digital media can support grassroots development efforts and the challenges involved.